Penerapan Model Pembelajaran Inkuiri Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Dinamika Atmosfer Kelas X Di SMA Negeri 2 Wonosari - fitri, Riska; Nurfaika, Nurfaika; Pratama, M. Iqbal Liayong (-, 2025)
This study aims to discuss the effectiveness of the application of the inquiry learning model in improving student learning outcomes in the material of atmospheric dynamics of class X at SMA Negeri 2 Wonosari. The study used a two-cycle Classroom Action Research (CAR) design with 23 students. Learning outcome tests, observations, and documentation were used to collect data. The findings showed that the inquiry learning model successfully improved conceptual understanding and student engagement in geography learning, as evidenced by an increase in learning completeness from 57.14% in cycle I to 89.29% in cycle II, an increase in the average score from 73.21 to 85.36, and an increase in learning activities from the category "quite active" to "very active".